2022
DOI: 10.3389/fphar.2022.905711
|View full text |Cite
|
Sign up to set email alerts
|

Ninjinyoeito improves social behavior disorder in neuropeptide Y deficient zebrafish

Abstract: Sociability is an essential component of the linkage structure in human and other vertebrate communication. Low sociability is defined as a poor social approach, including social withdrawal and apathy, and is implicated in a variety of psychiatric disorders. Ninjinyoeito (NYT), a traditional Japanese herbal medicine, has been used in the medical field. This study aimed to determine the effect of NYT on low sociality in NPY-KO zebrafish. NPY-KO zebrafish were fed a 3% NYT-supplemented diet for 4 days and subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Importantly, this area is a central hub of oxytocin neurons, and a homolog to the mammalian supraoptic nucleus of the hypothalamus, where CRH type‐2 receptors are coexpressed on oxytocin neurons 39,66 . In a separate study, it has been demonstrated that the expression of neuropeptide Y, which is involved in cell growth and homeostasis, can also negatively impact social interaction tendencies in zebrafish 112 . The deficiencies were recovered by the herbal medicine Ninjinyoeito, but this recovery did not induce changes in oxytocin levels, but it similarly affected CRH and dopamine precursor genes, suggesting that the activity of neuropeptides other than oxytocin also implicates the two systems.…”
Section: Social Affiliation: Perceptual Mechanisms Development and Ge...mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this area is a central hub of oxytocin neurons, and a homolog to the mammalian supraoptic nucleus of the hypothalamus, where CRH type‐2 receptors are coexpressed on oxytocin neurons 39,66 . In a separate study, it has been demonstrated that the expression of neuropeptide Y, which is involved in cell growth and homeostasis, can also negatively impact social interaction tendencies in zebrafish 112 . The deficiencies were recovered by the herbal medicine Ninjinyoeito, but this recovery did not induce changes in oxytocin levels, but it similarly affected CRH and dopamine precursor genes, suggesting that the activity of neuropeptides other than oxytocin also implicates the two systems.…”
Section: Social Affiliation: Perceptual Mechanisms Development and Ge...mentioning
confidence: 99%
“…39,66 In a separate study, it has been demonstrated that the expression of neuropeptide Y, which is involved in cell growth and homeostasis, can also negatively impact social interaction tendencies in zebrafish. 112 The deficiencies were recovered by the herbal medicine Ninjinyoeito, but this recovery did not induce changes in oxytocin levels, but it similarly affected CRH and dopamine precursor genes, suggesting that the activity of neuropeptides other than oxytocin also implicates the two systems. Nonetheless, the question for the anxiolytic oxytocin controls on dopaminergic signaling as a candidate system for the regulation of social motivation remains an open question.…”
Section: Stress-hormone and Reward-signaling Effects On Motivated Int...mentioning
confidence: 99%
“…Previous studies indicated that NYT ameliorated dementia or depression/anxiety [94][95][96] by increasing the levels of neurotrophic factors [94,97], attenuating the inhibition of neurogenesis [95,98], suppressing microglial overactivity [99], increasing cerebral blood flow [100], and enhancing cerebral glucose metabolism [92]. Furthermore, NYT improved diminished motivation [86,87,101,102] and suppressed the hypothalamic-pituitary-adrenal (HPA) axis by downregulating the sympathetic-adrenal-medullary (SAM) axis and GABA neurons to improve sociability [103].…”
Section: Psychological Frailtymentioning
confidence: 99%
“…They have established protocols for assessing sociability using the three-Chambers test ( Ariyasiri et al, 2019 ). Thus, they are suitable for drug discovery research and used in Kampo medicine research ( Kawabe et al, 2021 ; Kawabe et al, 2022 ). Recently, neuropeptide Y-knockout (NPY-KO) zebrafish were established as models for anxiety-like and low social behavior ( Shiozaki et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The zebrafish NPY amino acid sequence and the NPY function are very similar to the human NPY ( Singh et al, 2017 ; Shiozaki et al, 2020 ). The NPY-KO zebrafish showed low sociability in the three-Chambers test and exhibited anxiety-like behaviors such as freezing under acute stress ( Kawabe et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%